Beneficiary-centered management of irrigation systems: Retrospection on recent endeavors: Proceedings of the workshop held at the Irrigation Department, Colombo, Sri Lanka, 25th May 1995 - Haq, K.A.; Nandaratna, S.M.K.B. (International Irrigation Management Institute, 1996)
IN 1978, THE United States Agency for International Development (USAID) decided to assist the Government of Sri Lanka in improving the management of water in major irrigation projects in the dry zone. It was understood that this required building an adequate knowledge-base and new institutional capacities both of which take time but neither of which can be purchased 'off the shelf.' USAID and the Government of Sri Lanka recognized that a successful effort to improve water management could well take 20 years, but it would have to begin in a focused, concrete way, in a pioneering project that would begin to build up in-country knowledge and institutional capacity. In 1979, the government and USAID selected the Left Bank of the Gal Oya Irrigation System for rehabilitation. This planned change program was officially called the Gal Oya Rehabilitation and Water Management Project. The Irrigation Department (10) was appointed by the government as the project implementing agency. Technical assistance was to be obtained from the PRC Engineering consultants Inc., a U.S. engineering firm. Through a Letter of Understanding, the 10 was further assisted by the Agrarian Research and Training Institute (ARTI), which dealt with the socioeconomic components of the project. ARTI was assisted in this regard by the Rural Development Committee of Cornell University, USA. The project initially spanned 44 months (August 1979 to march 1984). The project life was subsequently extended by 21 months, until December 31,1985 as it needed more time to reach its assigned targets. With this policy objective, the Farmer Organization Program was included as one of the components of this major water management and rehabilitation project. The project assigned the establishment of farmer organizations (FOs) and the promotion of farmers' participation in these associations to ARTI. The main objective of this paper is to describe how these FOs evolved. The paper stresses that there was a cyclical trend of Fa evolution. It describes how FOs began and flourished at the initial stage of the project and the socio-administrative-climate that provided a conducive environment to such growth. Then it examines the crises and dynamics of the program's decline during its latter part.